Attitude profile of prospective UMRAH biology teacher students regarding green technology products - Fernando Adam; Pratama Yudi; Intasir M. Pemberdi; Siregar Eko Febri Syahputra; Sarkity Dios (SHS Web of Conferences)
The development of science and technology today has created various innovations in life, such as green technology. Raja Ali Haji Maritime University (UMRAH), as a higher education institution in Indonesia that produces prospective biology teachers, is responsible for instilling awareness in students about the importance of protecting the environment and implementing sustainability principles through the use of green technology products. However, the extent to which their attitudes towards these green technology products have yet to be widely disclosed. This study aims to determine the attitude profile of prospective biology teacher students at UMRAH towards green technology products. This descriptive study involved 105 new students of the UMRAH Biology Education Study Program in the last two years (2023-2024) as respondents. The instrument used to collect the data was a questionnaire using a Likert scale. Based on the research results that have been obtained, the attitude profile of prospective biology teacher students at UMRAH regarding green technology products is in the good category.